Possibilities of using ChatGPT artificial intelligence in the educational system (Herald of Journalism, 2025)
Today, humanity is at the stage of rapid and rapid development of digitalization. In the last decade, artificial intelligence has been influencing society in various fields.The purpose of the research work is to determine the significance, content, and function of the ChatGPT program by analyzing and comparing the widespread use of artificial intelligence in today's educational system.  As a research method, artificial intelligence has become an integral part of the new media system, to determine the effective strategy of introducing artificial intelligence to the field of education, learning experience, to evaluate, to make a scientific opinion.Today, humanity is at a stage of rapid and intensive development of digitalization. In recent decades, artificial intelligence has firmly entered our daily lives, changing society and influencing various spheres. In recent years, in the context of the constant development of information and communication technologies, the media landscape has undergone rapid changes. On the one hand, this increases the activity of media professionals, and on the other, it plays an important role in the modernization and renewal of journalism.The research methodology of the article is determined by the fact that artificial intelligence, algorithms and robots, and other technologies, along with risks, threaten the media, companies such as Minecraft, Facebook, Google and Microsoft are currently contributing to the development of artificial intelligence.At the end of the study, the scientific orientation of the ChatGPT chatbot program as a natural language processing tool controlled by artificial intelligence technology was demonstrated.This article discusses the main function of the ChatGPT program, its role in the information age, and the economic and social effects of natural language processing.The practical significance of scientific work lies in the fact that in the context of artificial intelligence, new media concepts such as "robotic journalism", "algorithmic journalism" or "automated journalism" are being implemented in journalism.
Keywords: ChatGPT, artificial intelligence, transformation, technological progress, program.